The Transition of Immigration Service Modernization in the Review of Law Number 6 of 2011 on Immigration - Novan Syahputra; Cokorde Istri Dian Laksmi Dewi; Benyamin Tungga (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The increase in international mobility requires innovations in immigration services that are fast, efficient, and secure. One of the innovations implemented by the Directorate General of Immigration Indonesia is the use of the autogate system, which allows immigration checks to be performed independently by travelers through passport scanning and biometric data. This system aims to expedite the inspection process, reduce queues, and enhance the accuracy and transparency of immigration surveillance. This study aims to analyze the implementation of the autogate system within the context of Indonesian immigration law, referring to Law Number 6 of 2011 on Immigration. The approach used covers the philosophical, legal, and sociological aspects of applying autogate as an instrument for modernizing immigration services. The results show that the use of this technology supports the principles of efficiency, transparency, and national security protection. However, technical challenges, regulations, and inter-agency data integration remain obstacles to its optimal implementation. Therefore, this study is expected to contribute to public policy and the refinement of a technology-based immigration system that is grounded in legal certainty and national interests. Keywords: Autogate System, Immigration, Technology